Abdominal wall allotransplantation - Molitor, Martin; Oliverius, Martin; Sukop, Andrej (Biomedical papers, 2018)
Allotransplantation of vascularized composite tissue is a new field of transplantation surgery. One application of this technique is abdominal wall transplantation used as a supplementary procedure to the transplantation of visceral organs in patients with abdominal compartment deficits. As abdominal wall closure problems are experienced in around 30-40% of such patients, peer reviewed conclusions on the viability of various options, are important for an informed choice of possible procedures. This review focuses on the abdominal wall allotransplantion procedure. Our search provided 35 appropriate references which we used to support our findings as follows: abdominal wall transplantation was performed in 33 patients at seven centres. Of these, 30 had a full thickness abdominal wall transplanted from the same donor, 3 from a second donor. Three had visceral organ transplants and in addition, the posterior sheet of the rectus muscle fascia. In summary, our findings were that abdominal wall allotransplantation does not jeopardize the outcome of visceral organs transplantation. There is no higher risk of complications or rejection of the visceral organs. There have been no fatalities as a direct result of complications due to abdominal wall transplantation. Finally, the transplanted abdominal wall may provide an early warning of rejection before diagnostic tests on the bowel are symptomatic.
Keywords: abdominal wall transplantation; vascularized composite allotransplantation